ISLAMISASI SENI DAN SENI ISLAMI: GERAKAN MANAKAH YANG LEBIH BERPELUANG? - Enoh Enoh (FISIP UIN SGD Bandung, 2018)
This article scrutinizes the issue of Islamization of art which becomes buzzwords lately. This writing also verifies a theory by Koentraraningrat that religion is a part of culture, so that religion is a domain of human reason. Here the writer exemplifies to an art called Dodod in Southern Banten. The consecutive issue, then, comes to light is a question of whether “Islamization of art” or “Islamic art” which is more likely to emerge. Temporary data found in the real world is that Islamization of art has already begun, even in a form of syncretism.